Mesoporous silica and alumina nanoparticles to improve drug delivery of pioglitazone on diabetic type 1 nephropathy in rats - Jaleh Varshosaz; Saeedeh Ahmadipour; Armin Dezhangfard (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: Diabetic nephropathy leads to end-stage renal disease. The present study aimed to evaluate the prophylactic effect of pioglitazone-loaded mesoporous silica and alumina scaffold on renal function and the underlying mechanisms in streptozotocin-induced diabetic rats. Experimental approach: The mesoporous nanoparticles were synthesized by chemical methods from tetraethylorthosilicate and aluminum isopropoxide and characterized by Fourier transform infrared spectroscopy, X-ray diffraction, and scanning electron microscopy. The soaking method was applied to load pioglitazone into the mesoporous silica and alumina. Subsequently, the most capable formulation was evaluated for lipid profile, blood glucose, renal function biomarkers, malondialdehyde, and kidney histopathological changes in diabetic rats. Findings/Results: Pioglitazone loaded in the mesoporous included a superior release of about 80%. No interaction was observed in Fourier transform infrared spectroscopy and X-ray diffraction was shown crystalline. Scanning electron microscopy showed the size of the nanometer in the range of 100 - 300 nm. Mesoporous silica containing the drug significantly decreased urinary parameters, triglycerides, low-density lipoprotein, blood urea nitrogen, blood glucose, malondialdehyde, and creatinine. In addition, it showed increased high-density lipoprotein, significantly. The renal histopathological changes indicated improvement compared with the untreated diabetic group. Conclusion and implications: It was concluded that the mesoporous was potent to serve as a promising drug carrier and a platform aimed at the delivery of poorly water-soluble drugs for improving oral bioavailability. Furthermore, it has the potential to provide a beneficial effect on the changes in diabetic parameters.